Síntese quimioenzimática do apremilast usando lipases e cetorredutases - Vega, Kimberly Benedetti (2020)
Apremilast (S)-1 is a commercially known drug under the brand name Otezla® and is used to treat patients with moderate to severe psoriasis or active psoriatic arthritis. This drug is relatively recent and was approved by the FDA only in 2014. In this project, we describe the development of a biocatalytic approach for the synthesis of apremilast and the key step was to obtain a chiral intermediate, the alcohol (R)-14, (R)-1-(3-ethoxy)4-methoxyphenyl)-2-(methylsulfonyl)ethanol. The alcohol (R)-14 was obtained via two enzymatic approaches, one using ketoreductases and one using lipases. Bioreduction of ketone 12, 1-(3-ethoxy-4-methoxyphenyl)-2-(methylsulfonyl)ethanone, in the presence of KRED-P2-D12, led to alcohol (R)-14 with 48% conversion and enantiomeric excess 93%. Kinetic resolution of racemic ester rac-15, 1-(3-ethoxy-4-methoxyphenyl)-2-(methylsulfonyl)ethyl acetate, by hydrolytic process catalyzed by lipase from Aspergillus niger led to alcohol (R)-14 with enantiomeric excess > 99%, 50% conversion and enantioselectivity (E) > 200. Kinetic resolution of rac-15 was only effective in the presence of 20% n-butanol relative to phosphate buffer medium (pH 7). Lipase from Aspergillus niger has proven to be a robust biocatalyst because it provides the intermediate alcohol (R)-14 in enantiomerically pure form and with a maximum conversion of 50%. The best condition for resolution of rac-15 was lipase/substrate 3:1, in PO43- (pH 7) buffer with 20% n-butanol, 6 h of reaction time at 45 ° C. Subsequently, enantiomerically pure alcohol (R)-14 reacted with phthalimide 19, 4-acetylamino-isoindol-1,3-dione, via Mitsunobu reaction, yielding apremilast in 65% yield and enantiomeric excess 51%.